O princípio da boa-fé objetiva no direito de família - Gurgel, Fernanda Pessanha do Amaral (2008)
In light of the civil constitutional order, the objective of this work is to interpret the principle of the objective good faith applied to the new family concept. The family, as a central part of the development of the personality and the promotion of the dignity of its members, must be regulated by a legal order that is able to influence its relations. By this point of view it must provide for standards of behaviour and establish, by means of concrete measures, the incorporation of the constitutional values. In this context it is necessary to analyse the concept of objective good faith, recognising it as a legal principle containing general ethical values with influence over various intersubjective relations. In family law, the existence of elements of objective good faith is recognised, which is responsible for the creation of specific obligations specifically directed to the formation and maintenance of a family environment guided by respect, cooperation, kindness, trust and solidarity. In this way, the occurrence of objective good faith in the existential and patrimonial relations of a family results in the obligation for the family members to behave in a loyal, harmonic and balanced way and to refrain from exercising their legal rights in an abusive manner. The concrete application of the principle of the objective good faith is an efficient mechanism for solving various conflicts arising from family affairs. In this way, in order to materialise the objective good faith it is fundamental that it is in connection with other legal institutions, such as the prohibition of enrichment without cause, illegal enrichment and civil liability. All these questions lead us to a family legislation that is harmonic with the social ethical objectives of the new legal order